Gender And Design: Gender Bias In Agrotechnology - Silvia Senjaya; Yayuk Yuliati (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2021)
Abstract —  The role of women as farmers has existed in the history of human life for centuries. However, the Green Revolution made the role of women who were previously trusted to select seeds, weed, plant, fertilize, harvest and pound rice replaced by the role of technology. As with other designs and technologies, there has been a gender bias, so the researchers suspect that there is a gender bias in the design of agrotechnologywhich has an impact on the marginalization of female farmers. Through a literature review, researchers explored gender bias in design of agrotechnology and its impact on female farmers. Design of agrotechnology is still gender biased because it was designed without taking women's ergonomics. In fact, women have different ergonomic characteristics from men, but that does not mean they do not have the capacity to farm.  Feminization of agriculture will be a profitable job opportunity for women if it is accompanied by the feminization intervention of agricultural machine and tool. Keywords: gender bias, design, agrotechnology, agriculture, female farmer